MEMBANGUN WARGA NEGARA YANG BAIK DALAM KELUARGA - Siti Arifah Asri Amir; Debi Yuliana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Based on current family life, there are many children living in Nagari Tanjung Bonai, North Lintau Buo District, who have not been able to understand what a good citizen is. The aims of this study are (1) to identify and describe the role of the family in building good citizens in Tanjung Bonai Village (2) to identify and describe the factors causing the lack of family role in building good citizens in Tanjung Bonai Village. This type of research is qualitative. In this study, the data collection techniques used were observation and interviews. Research informants were conducted by purposive sampling. To ensure the validity of the data, the source triangulation technique was used. As well as data analysis techniques using data reduction steps, data presentation and finally drawing conclusions. The research findings show that (1) The role played by the family in the context of building good citizens has not been carried out optimally. This can be seen from the number of children who have not been able to understand and know what is meant by a citizen. (a) Parental Roles (b) Marriage Roles. (2) Many factors are the cause of the lack of the role of the family in building good citizens: (a) Families are less able to provide understanding Families still have a lack of understanding of the importance of building good citizens (b) Lack of understanding owned by families With family and parental knowledge that is still low on the importance of building good citizens, it can be one of the factors causing the lack of family role in building good citizens.Keywords: Family, Good Citizen